The 'Check Out' Impulse: Unveiling the Role Of Cognitive Assimilation and Arousal in the Influence of Streamers on Impulse Buying Intentions on TikTok Live - Kadek Krisma Adijaya; Ni Putu Nina Eka Lestari (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of streamer interaction (SI) and streamer attractiveness (SA) on impulsive buying intention (IPI) by considering the mediating roles of cognitive assimilation (CA) and emotional arousal (AR) in the context of TikTok live streaming. The results of data analysis and hypothesis testing reveal that SI and SA have a positive and significant effect on IPI, CA, and AR. Furthermore, CA and AR are found to significantly influence IPI, with AR being the most dominant factor driving impulsive buying intention. The study also shows that CA and AR serve as significant mediators in the relationship between SI, SA, and IPI. These findings confirm that interaction quality, personal attractiveness, and emotional stimulation from streamers play an essential role in shaping the shopping experience that drives spontaneous purchasing decisions on live streaming platforms.